Capital Structure, Profitability, Sales Growth: Firm Value with Managerial Ownership as a Moderating Variable - Ramadhani, Zahra Rizqia; Nawirah (Gorontalo Accounting Journal, 2026)
This study aims to determine how capital structure, profitability, and sales growth affect firm value, with managerial ownership as a moderating factor, in food and beverage companies listed on the Indonesia Stock Exchange from 2021 to 2024. From a total sample of forty-four food and beverage companies, one hundred and seventy-six were selected as observation locations. The quantitative approach uses moderation analysis and a panel-data regression model (Random Effects Model) for data analysis. The results of this study indicate that sales growth does not affect firm value. In contrast, capital structure and profitability have a partial effect. Managerial ownership factors can moderate the relationship between capital structure and profitability variables on firm value. Still, they cannot moderate the relationship between sales growth and firm value.